Tanshinone IIA inhibits apoptosis in the myocardium by inducing microRNA-152-3p expression and thereby downregulating PTEN - Zhang, Zhen (Am J Transl Res, 2016)
Progressive loss of cardiac myocytes through apoptosis contributes to heart failure (HF). In this study, we tested whether tanshinone IIA, one of the most abundant constituents of the root of Salvia miltiorrhiza, protects rat myocardium-derived H9C2 cells against apoptosis. Treatment of H9C2 cells with tanshinone IIA inhibited angiotensin II-induced apoptosis by downregulating the expression of PTEN (phosphatase and tensin homolog), a tumor suppressor that plays a critical role in apoptosis. Furthermore, tanshinone IIA was found to inhibit PTEN expression by upregulating the microRNA miR-152-3p, a potential PTEN regulator that is highly conserved in both rat and human. Notably, the antiapoptotic effect of tanshinone IIA was partially reversed when H9C2 cells were transfected with an inhibitor of miR-152-3p. Collectively, our findings reveal a previously unrecognized mechanism underlying the cardioprotective role of tanshinone IIA, and further suggest that tanshinone IIA could represent a promising drug candidate for HF therapy.